1900 Vt. Acts and Resolves 145, No. 162, § 42. - (:unkn) unknown (My University, 1900)
Said board of fire wardens may inspect the manner of manufacturing and keeping gun powder, lime, ashes, matches, lights, fireworks or combustibles[.]
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER